Cryptanalysis and design of lightweight symmetric-key cryptography - Sim, Siang Meng (2018)
Lightweight cryptography has been a rising topic along with the global development of very constrained computing devices, for which conventional cryptographic algorithms are often too resource-consuming to fit the use-cases such as RFID tags. Conducting cryptanalysis gives us better understanding on how to protect against adversaries. In the first part of this thesis, we analyse two lightweight symmetric-key primitives - JAMBU and Midori. For both primitives, we found practical attacks. Studying the building blocks of ciphers is essential for designing cryptographic primitives. In the second part of this thesis, we look into the components of Substitution-Permutation Network based block ciphers, namely the diffusion matrix and the S-box. We found new efficient components that ensure strong security properties. Combining our experience acquired in cryptanalysis and our knowledge of the cryptographic components, we are ready to design new ciphers. In the final part of this thesis, we propose two new block ciphers, SKINNY and GIFT, aiming at lightweight applications. They offer excellent performance and security against state-of-the-art cryptanalysis techniques.